1996
DOI: 10.1046/j.1365-2249.1996.d01-626.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to proteinase 3 mediate expression of vascular cell adhesion molecule-1 (VCAM-1)

Abstract: VCAM‐1 was first identified as an adhesion molecule induced on human endothelial cells (HEC) by inflammatory cytokines such as IL‐1, tumour necrosis factor (TNF), and lipopolysaccharide (LPS). The molecule binds to a variety of leucocytes, including B cells, T cells, basophils, eosinophils and monocytes. Vascular expression of VCAM‐1 has been associated with a number of disease states, including rheumatoid arthritis and vasculitis. The detection of antineutrophil cytoplasmic antibodies (ANCA), especially to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…In systemic vasculitis, there has been evidence suggesting ANCA plays an important role in pathogenesis. Anti-PR3 antibodies have been shown to enhance the activation and adhesion of neutrophils (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In systemic vasculitis, there has been evidence suggesting ANCA plays an important role in pathogenesis. Anti-PR3 antibodies have been shown to enhance the activation and adhesion of neutrophils (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Activated complement products, antineutrophil cytoplasmic antibody binding to their cognate enzymes expressed at the surface of neutrophils or endothelial cells, and proinflammatory cytokines released upon T lymphocyte and macrophage activation have been demonstrated to up-regulate endothelial adhesion molecule expression or to increase leukocyte integrin function (17)(18)(19). Previous studies have shown that, at some point, endothelial adhesion molecules for leukocytes are expressed in inflamed vessels from patients with vasculitis, suggesting their participation in the development of vascular inflammation by mediating leukocyte recruitment in the vessel wall (17,(20)(21)(22).…”
mentioning
confidence: 99%
“…Moreover, the presence of PR3-specific mRNA was detected in cultured cytokine-treated human endothelial and renal TECs (26,27), as well as in kidney biopsies, with distal tubules as well as glomerular epithelia being strongly positive for PR3 message (28). While binding of c-ANCA to endothelial cells is followed by expression of adhesion molecules (29) and activation of signaling responses such as phosphoinositide hydrolysis with progressive loss of endothelial barrier properties (30), the effects of c-ANCA interaction with renal TECs are largely unknown. Such interaction may, however, be of major interest, as renal TEC may well be involved in inflammatory events, by expression of adhesion molecules, promotion of leukocyte recruitment, and synthesis of inflammatory mediators (6 -10).…”
Section: W Egener's Granulomatosis (Wg)mentioning
confidence: 98%